Physician-related barriers to communication and patient- and family-centred decision-making towards the end of life in intensive care: a systematic review - Visser, Mieke (Crit Care, 2014)
INTRODUCTION: Although many terminally ill people are admitted to an intensive care unit (ICU) at the end of life, their care is often inadequate because of poor communication by physicians and lack of patient- and family-centred care. The aim of this systematic literature review was to describe physician-related barriers to adequate communication within the team and with patients and families, as well as barriers to patient- and family-centred decision-making, towards the end of life in the ICU. We base our discussion and evaluation on the quality indicators for end-of-life care in the ICU developed by the Robert Wood Johnson Foundation Critical Care End-of-Life Peer Workgroup. METHOD: Four electronic databases (MEDLINE, Embase, CINAHL and PsycINFO) were searched, using controlled vocabulary and free text words, for potentially relevant records published between 2003 and 2013 in English or Dutch. Studies were included if the authors reported on physician-related and physician-reported barriers to adequate communication and decision-making. Barriers were categorized as being related to physicians’ knowledge, physicians’ attitudes or physicians’ practice. Study quality was assessed using design-specific tools. Evidence for barriers was graded according to the quantity and quality of studies in which the barriers were reported. RESULTS: Of 2,191 potentially relevant records, 36 studies were withheld for data synthesis. We determined 90 barriers, of which 46 were related to physicians’ attitudes, 24 to physicians’ knowledge and 20 to physicians’ practice. Stronger evidence was found for physicians’ lack of communication training and skills, their attitudes towards death in the ICU, their focus on clinical parameters and their lack of confidence in their own judgment of their patient’s true condition. CONCLUSIONS: We conclude that many physician-related barriers hinder adequate communication and shared decision-making in ICUs. Better physician education and palliative care guidelines are needed to enhance knowledge, attitudes and practice regarding end-of-life care. Patient-, family- and health care system–related barriers need to be examined. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13054-014-0604-z) contains supplementary material, which is available to authorized users.